Mapping The Quality of pH, Lactic Acid, Total Plate Count, and The Residu of Tetracycline Antibiotic in Chicken Slaughterhouses, Chicken Meat in Jemberdistrict, East Java, Indonesia - risxi, Galuh; Kalsum, Umi; Ali, Usman (Unpad Press, 2024)
The purpose of this study was to determine the quality mapping of pH, lactic acid, total plate count and tetracycline antibiotics in broiler meat found in the Patrang districts' a CRD, or completely random design and a descriptive analytic case study methodology were both used in this investigation with 9 experimental units and 3 replications. Sampling of broiler meat was taken from at 01.00 WIB. The locations used were 3 out of 6 Traditional. Each sample was taken from each 3 times, so that the sample size used in the 3 was 9 experimental units. Parameters observed were TPC, antibiotic residues, pH value and lactic acid levels ANOVA was used to statistically evaluate the data, and then the SPSS program was used to perform the BNT test. The results demonstrated a substantial effect on the parameters of lactic acid, pH and microbiology. Tests at 3 traditional of antibiotic residues showed no residue of tetracycline antibiotics. The conclusion of this study shows that the quality mapping of pH, lactic acid, TPC and tetracycline antibiotics in in the Patrang area, Jember City still meets the findings demonstrated a substantial.